Sustainablility of multi-generations dwelling: condition survey on old Malay traditional houses in Kuala Kangsar, Perak - Kamaruddin, Zumahiran; Abdul Latip, Nurul Syala; Sulaiman, Nurhafizatulakmar (2015)
The preservation and conservation of Malay traditional house in Kuala Kangsar, Perak, Malaysia has become major research interests in past decades. However, very little research was conducted to investigate on the houses focusing on the components and materials including physical spaces that accommodate universal needs of their occupants. Most of the old houses are originally built on stilts and uses lightweight construction with elevated steps and floors. Many of them had gone through upgrading by renovation and restoration because of safety reason and decay exposure. Therefore, the aim of this study is to investigate the condition of the physical components and spatial elements of the houses that have gone through renovation to accommodate universal needs of their residents. The objectives of the study are: 1) to identify the condition status of the components found in the selected Malay traditional houses, 2) to examine the nature and extent of changes made to the houses for disabled requirements. Qualitative data were collected through condition survey and interviews with the house residents during site visit. A total of 12 Malay traditional houses in Kuala Kangsar, Perak were selected for condition survey and visual inspection. They are among the surviving oldest houses in this region. The method of documentation involved recording the house’s historical background and current condition, inventory of the physical components, spatial and material changes. The study found that appropriate action has been taken by the residents of the houses not only to safeguard their valuable heritage but also to ensure the needs of disable residents especially the elderly are well accommodated. The findings would assist the local community to implement further management plan for preservation of the traditional houses, whilst ensuring the continuous survival of the houses that reflect heritage value as well as the social value of the multi-generation residents.